Epigallocatechin-3-Gallate Promotes the Growth of Mink Hair Follicles Through Sonic Hedgehog and Protein Kinase B Signaling Pathways - Zhang, Haihua; Nan, Weixiao; Wang, Shiyong; Song, Xingchao; Si, Huazhe; Li, Tong; Li, Guangyu (Frontiers in Pharmacology, 2018)
Background: Hair follicles play an essential role in the growth of hair. Epigallocatechin-3-gallate (EGCG), a catechin polyphenol in green tea, has various bioactivities. The present study aims to evaluate the effect of EGCG on the growth of mink hair follicles and investigate the possible molecular mechanisms. Methods: The length of hair follicles was recorded up to 6 days in presence of 0.1-5 μM EGCG. Primary dermal papilla cells (DPCs) and outer root sheath cells (ORSCs) were treated with 0.25-4 μM EGCG, and their growth was evaluated by MTT assay and cell cycle detection. The levels of key molecules in sonic hedgehog (Shh) and AKT signaling pathways were further assessed by quantitative real-time PCR, western blot and immunofluorescence. To determine the involvement of Shh and AKT pathways in EGCG-mediated growth-promotion of ORSCs and DPCs, Shh pathway inhibitors cyclopamine and GANT61 or AKT pathway inhibitor LY294002 were employed, and then cell proliferation and cell cycle were analyzed. Results: Data from ex vivo culture showed that, in presence of 0.5-2.5μM EGCG, the growth of mink hair follicles was promoted. In vitro, the proliferation of DPCs and ORSCs was enhanced by 0.5-4 μM EGCG treatment. More cells entered S phase upon treatment of EGCG, accompanied with upregulation of cyclin D1 and cyclin E1. Furthermore, when exposed to EGCG, the Shh and AKT signaling pathways were activated in both hair follicles and primary DPCs and ORSCs. Inhibiting either of these two pathways partly reversed the effect of EGCG on proliferation and cell cycle of DPCs and ORSCs. Conclusion: EGCG promotes the growth of mink hair follicles at concentrations of 0.5-2.5μM. This growth-promoting effect of EGCG may be associated with the increased proliferation of DPCs and ORSCs through activating Shh and AKT signaling pathways.